Upaya Pencegahan Risiko Hipertrigliseridemia melalui Penapisan Kadar Trigliserida di Sekolah Kristen Kalam Kudus 2,Jakarta - Sutedja, Gina Triana; Santoso, Alexander Halim; Destra, Edwin; Pratama, Aditya; Soebrata, Linginda (PPNI UNIMMAN, 2025)
Hypertriglyceridemia is a metabolic condition characterized by elevated triglyceride levels in the blood and is closely related to cardiovascular risk and metabolic syndrome. Routine blood tests play an important role in detecting unnoticed lipid disorders, especially in individuals without clinical symptoms. Triglyceride screening was performed on 91 adult participants using the point-of-care testing (POCT) method. Education was provided through leaflets containing information on lifestyle and dietary patterns that affect triglyceride levels. The results were classified and analyzed to identify risk distribution and as a basis for health education. The mean triglyceride level of participants was 137.8 ± 77.1 mg/dL (range 45–463 mg/dL). Most participants showed values ​​within the normal range, but individuals with very high levels were found, indicating hidden metabolic risks that require clinical attention. Early detection of triglyceride levels accompanied by education based on examination results is a strategic step in preventing hypertriglyceridemia. Community intervention through education and the formation of healthy habits contributes to controlling the risk of non-communicable diseases in the adult population.